Selected papers from the International Scientific Conference on Numerical Heat Transfer 2005 [ - Bialecki, Ryszard A.; Nowak, A. J. (International journal of numerical methods for heat & fluid flow, 2008)
Selected papers presented during the International Scientific Conference on Numerical Heat Transfer (NHT2005). The papers demonstrate, on one hand, an overview of the conference topics and, on the other hand, to document the most important advances in numerical heat transfer.